Anthropometrics and prognosis in diffuse large B‐cell lymphoma: a multicentre study of 653 patients. (31st January 2017) - Bendtsen, Mette Dahl; Munksgaard, Peter Svenssen; Severinsen, Marianne Tang; Bekric, Eric; Brieghel, Christian; Nielsen, Kristina Buchardi; Brown, Peter de Nully; Dybkær, Karen; Johnsen, Hans Erik; Bøgsted, Martin; El‐Galaly, Tarec Christoffer
Abstract: Objective: The impact of body mass index (BMI) and body surface area (BSA) on survival in diffuse large B‐cell lymphoma (DLBCL) is controversial. Recent studies show superior outcomes for overweight and obese patients. Patients and methods: A total of 653 R‐CHOP(‐like)‐treated DLBCL patients were included in this retrospective cohort study. Patients, baseline clinicopathologic characteristics and treatment information were retrieved from the Danish Lymphoma Registry. Anthropometric measures were obtained from chemotherapy prescription charts. Results: Underweight (BMI <18.5 kg/m 2 ) was associated with significantly worse progression‐free survival (PFS) for male patients only in sex‐stratified analyses (HR 3.92, 95% CI: 1.57–9.75, P = 0.003, for males; HR 1.65, 95% CI: 0.90–3.02, P = 0.107, for females). In multivariate analyses, underweight was associated with worse PFS for both sexes (HR 5.34, 95% CI: 2.07–13.79, P = 0.001, for males; HR 2.14, 95% CI: 1.12–4.08, P = 0.021, for females). Similar results were obtained in analyses of overall survival. In crude analyses, BSA <1.8 m 2 was associated with worse PFS for men and women (HR 1.65, 95% CI: 1.03–2.65, P = 0.039, for men; HR 1.62, 95% CI: 1.03–2.56, P = 0.037, for women). In multivariate analyses, however, these associations diminished. Conclusions: Our study demonstrates that underweight DLBCL patients have worse outcomes following R‐CHOP as compared to normal as well as overweight patients.